Power to the Paperwork? Mandatory Financial Sanctions and the Bureaucratic Means to Racially Unequal Ends. (July 2021) - Henricks, Kasey
Few studies that disentangle the relationship between race, crime, and punishment have turned to administrative documents as a central site of power. Speaking to this omission, I use a case study of mandatory financial sanctions in the Criminal Division of the Cook County Circuit Court in the State of Illinois. The analysis draws upon a sample of 89 sanctions imposed upon conviction, at the state and county levels, to identify three bureaucratic aspects that sustain racial inequality. One, these sanctions are represented in ways that abstract the conviction process from its highly racialized context. Two, these sanctions enable legal actors to enact a multilevel mode of decision making, combining compulsory and discretionary judgment, that entrenches racial bias within the broader legal organization of punishment. And three, these sanctions redistribute the operational costs of justice through earmarks onto those who are processed through the system (i.e., disproportionately people of color). Altogether, these bureaucratic aspects paradoxically intensify racial stratification in ways that are seemingly nonracial.